Recent Advances in Psychopathology in Neurodevelopmental Disorders: From Bench to Bedside - Deb, Shoumitro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Psychopathology, including functional psychiatric disorders, such as schizophrenia, bipolar disorder, major depressive disorder and anxiety disorders, and also dementia and challenging behaviour, is common in people with neurodevelopmental disorders (NDDs), such as intellectual and developmental disabilities (IDD), autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), and is the cause for a major public health concern. Much research has been conducted in the last three decades to understand this issue and develop effective interventions. Still, a lot remains unknown, for which high-quality translational research is urgently needed. In this Special Issue, we drew together research on recent advances addressing these issues. The areas covered included life expectancy among people with and without intellectual disabilities, the social and emotional development of people with intellectual disabilities and ASD, the influence of external environmental factors in determining aggressive behaviour in people with intellectual disabilities, parent and child training for children with autism and intellectual disabilities, how the presence of deafness influences quality of life, the views of prescribers on the deprescribing of antipsychotics among adults with intellectual disabilities, the views of people with intellectual disabilities who took part in the deprescribing, the views of direct-care workers on the causes of challenging behaviours in people with intellectual disabilities, and the validation of tools to detect cognitive decline in adults with intellectual disabilities.